Ruthenium–Arene–β‐Carboline Complexes as Potent Inhibitors of Cyclin‐Dependent Kinase 1: Synthesis, Characterization and Anticancer Mechanism Studies. Issue 36 (22nd July 2013) - He, Liang; Liao, Si‐Yan; Tan, Cai‐Ping; Ye, Rui‐Rong; Xu, Yu‐Wen; Zhao, Meng; Ji, Liang‐Nian; Mao, Zong‐Wan
Abstract A series of RuII–arene complexes (1–6) of the general formula [(η6‐arene)Ru(L)Cl]PF6 (arene=benzene or p‐cymene; L=bidentate β‐carboline derivative, an indole alkaloid with potential cyclin‐dependent kinases (CDKs) inhibitory activities) is reported. All the complexes were fully characterized by classical analytical methods, and three were characterized by X‐ray crystallography. Hydrolytic studies show that β‐carboline ligands play a vital role in their aqueous behaviour. These complexes are highly active in vitro, with the most active complex 6 displaying a 3‐ to 12‐fold higher anticancer activity than cisplatin against several cancer cell lines. Interestingly, the complexes are able to overcome cross‐resistance to cisplatin, and show much lower cytotoxicity against normal cells. Complexes 1–6 may directly target CDK1, because they can block cells in the G2M phase, down‐regulate the expression of CDK1 and cyclin B1, and inhibit CDK1/cyclin B in vitro. Further mechanism studies show that the complexes can effectively induce apoptosis through mitochondrial‐related pathways and intracellular reactive oxygen species (ROS) elevation.